Development of Islamic Religious Education Teaching Modules Based on Local Wisdom Story Babad Kebo Kicak Karang Kejambon - Dwi Rohmah Alfinadziroh; Machnunah Ani Zulfah; Muhammad Fodhil; Muhamad Khoirur Roziqin (Permata : Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the development of Islamic Religious Education teaching modules based on local wisdom of the Babad Kebo Kicak Karang Kejambon story which includes (1) the planning process for developing Islamic Religious Education teaching modules based on local wisdom of the Babad Kebo Kicak Karang Kejambon story (2) the effectiveness of developing Islamic Religious Education teaching modules based on local wisdom of the Babad Kebo Kicak Karang Kejambon story. The method used in this study is research and development (R&D) using the Thiagarajan 4D model, namely define, design, development, and disseminate. The results of the study showed a validity score of 80% from learning practitioner experts, 89% from material experts, and 90% from teaching module review experts. The effectiveness test using pre-test and post-test showed that this teaching module was effective. The small-scale test obtained a score of 68.46%, while the large-scale test obtained a score of 71.7%, with an increase of 3.24%. In addition, the student response questionnaire to the teaching module showed that this teaching module was very interesting, with a score of 91.6% in the small-scale test and 96.94% in the large-scale test, indicating an increase of 5.34%. The practical implications of this study, the success of the validation and trial of the module with very good results (expert validation 80-90% and student response 91.6-96.9%) indicate that the integration of local wisdom in Islamic Religious Education learning can be an effective approach to improving student understanding. Keywords: Development; Teaching Module; Islamic Religious Education; Local Wisdom